Pengaruh Tingkat Emosi, Kecukupan Gizi dan Kebiasaan Hidup Ibu Hamil terhadap Perkembangan Janin - Nuramalia. M; Nuranggun Grafita; Madina Makmur; Meldini Indri Mayora (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of emotional level, nutritional adequacy and living habits of pregnant women on fetal development. The type of research used is expos facto research. The Facto Exposure Method is a research method for examining the cause-effect relationship of an event. From these causal linkages, new possibilities will be found that can be used as indicators in the research process. Based on the research results show that the emotional level of the mother during pregnancy can also affect the development of the fetus until the birth process, because this can cause an irregular supply of fetal oxygen, which can cause problems in the fetus. the emotional level causes irregular contractions so that the birth process will be difficult. An imbalance in nutrient consumption, especially a lack of intake of one or more nutrients during pregnancy can increase the risk of complications in pregnant women such as chronic energy deficiency (CED), anemia, difficult and long labor and susceptibility to infectious diseases (Ernawati, 2012). Meanwhile, the habits of pregnant women can affect the fetus based on the level of activity carried out, healthy living habits will have a positive impact on fetal development. However, bad habits and anxiety will affect the psychology and development of the fetus.